Dynamic recruitment of amino acid transporters to the insect/symbiont interface. Issue 6 (16th February 2014) - Duncan, Rebecca P.; Husnik, Filip; Van Leuven, James T.; Gilbert, Donald G.; Dávalos, Liliana M.; McCutcheon, John P.; Wilson, Alex C. C.
Abstract Symbiosis is well known to influence bacterial symbiont genome evolution and has recently been shown to shape eukaryotic host genomes. Intriguing patterns of host genome evolution, including remarkable numbers of gene duplications, have been observed in the pea aphid, a sap‐feeding insect that relies on a bacterial endosymbiont for amino acid provisioning. Previously, we proposed that gene duplication has been important for the evolution of symbiosis based on aphid‐specific gene duplication in amino acid transporters (AATs), with some paralogs highly expressed in the cells housing symbionts (bacteriocytes). Here, we use a comparative approach to test the role of gene duplication in enabling recruitment of AATs to bacteriocytes. Using genomic and transcriptomic data, we annotate AATs from sap‐feeding and non sap‐feeding insects and find that, like aphids, AAT gene families have undergone independent large‐scale gene duplications in three of four additional sap‐feeding insects. RNA‐seq differential expression data indicate that, like aphids, the sap‐feeding citrus mealybug possesses several lineage‐specific bacteriocyte‐enriched paralogs. Further, differential expression data combined with quantitative PCR support independent evolution of bacteriocyte enrichment in sap‐feeding insect AATs. Although these data indicate that gene duplication is not necessary to initiate host/symbiont amino acid exchange, they support a role for gene duplication in enabling AATs to mediate novel host/symbiont interactions broadly in the sap‐feeding suborder Sternorrhyncha. In combination with recent studies on other symbiotic systems, gene duplication is emerging as a general pattern in host genome evolution.